Epidemiology study of the association between silica and blood Heme Oxygenase-1 levels with silicosis - ด่านไพบูลย์ อนงค์ศิลป์; หลิวเสรี วิทยา; ชัยสุวรรณ ชาญณรงค์; ขันติพงศ์ เจียรนัย; คชาอนันต์ ศุภกิจ; นามบุญมี โกวิทย์ (Disease Control Journal, 2015)
The aim of retrospective cohort analytic study was to determine the correlation between silica dust level, blood Heme Oxygenase-1 (HO-1) and silicosis disease. The interview, air sampling for detection silica dust level, blood HO-1 analysis and chest x-ray were performed on mortar and non-mortar worker at Bansang, Phayao Province. The number of volunteer was 236 cases divided to silica exposure group (mortar worker) 117 cases and non-silica exposure group (non-mortar worker) 119 cases. The data were analyzed using descriptive statistic, percentage, average and binary logistic regression analysis. The results demon¬strated the average of silica dust level in atmospheric workspace of mortar worker was 12.11 mg/cm3 and the maximum was 20.41 mg/cm3. The average of HO-1 on mortal and non-mortar worker were 110.43 and 90.30 ng/ml, respectively. Moreover, this study revealed the silica dust level on atmospheric workspace had the statistic significantly with silicosis disease (p<0.005) by the elevation of silica level lmg/cm3 affected to risk of silicosis 1.218-fold on exposure case comparing with worker who exposed less than 1 mg/cm3. Also, the blood HO-1 level was statistic significantly with silicosis disease (p<0.005). The worker who had the decreasing of blood HO-1 1 ng/ml risked to silicosis 0.977-fold. As well as, this study discovered the statistic significantly correlation between silicosis and duration of work (p<0.005) that the increasing of work time every one year risked to silicosis 1.065-fold. From our studies, the HO-1 level, duration of wok and amount of silica dust related with the progression of silicosis, however, this study was performed on short time so the long time study including evaluated the specificity and sensitivity of test for improvement the screening of early silicosis will be researched.